A proposed crowdfunding framework for developing waqf land in Malaysia - Hapsari, Meri Indri (Kulliyyah of Economics and Management Sciences International Islamic University Malaysia, 2020)
Waqf institutions in many Muslim countries including in Malaysia are facing financial constraints in developing waqf land. This study has developed Crowdfunding Waqf Model (CWM) that is aimed to offer a sustainable model of financing source for waqf institutions to meet their financial constraint in developing waqf land. In this model, the State Religious Islamic Council (SIRC) will collaborate with crowdfunding platforms will raise funds from the crowd funders in the form of money donation. CWM will provide financing services to waqf institution by forming donation money through donation-based and reward-based crowdfunding. Thus, this model suggests ways of improving and meeting the need of waqf institution in Malaysia by providing affordable financing services. This new model is utilized crowdfunding consider with its ability to finance various charitable projects with focus on gather many small donations rather than requesting a single large sum from funding agency or traditional financial institutions. The study uses mixed method (interview and survey) approach. The interview was conducted to validate CWM in terms of its suitability, applicability and its prospects. The findings from the interviews revealed that the experts have positive perception and attitude towards the proposed CWM. In addition, the experts opine that CWM is applicable in Malaysia and has tremendous benefits for developing waqf land. Similarly, the results from the survey, analysed using Structural Equation Modeling (SEM) based on Technology Acceptance Model (TAM) hypothesized that behavioural intention of crowd funders to use CWM is significantly and positively impacted by “perceived usefulness”, “perceived ease of use” and “perceived ease of use” on perceived usefulness”. This thus suggests that when crowd funders have a more positive view about “the usefulness” and “ease of use” of CWM, the stronger their intention to be involved in CWM to assist waqf institutions to develop waqf land in Malaysia.